The effect of pollution production in gas burner combustion system using Flat Vane Radial Air Swirler - Izwan Mahmud (Universiti Malaysia Perlis, 2008)
A gas burner system with flat vane radial air swirler with vane angle of 20°, 40° and 60° has been investigated to compare which swirler produce less Carbon Monoxide. All tests were conducted using Butane gas. Fuel was injected at an upstream position of the swirler outlet using gas torch that function as a central fuel injector. The overall study shows that bigger swirler vane angle produce a higher temperature profile compared to the smaller swirler vane angle and produce less Carbon Monoxide. Swirler vane angle also influences the stability of the flame and also the swirl flow.